2002
DOI: 10.1002/jcb.10252
|View full text |Cite
|
Sign up to set email alerts
|

Glucose‐dependent regulation of osteoclast H+‐ATPase expression: Potential role of p38 MAP‐kinase

Abstract: Bone resorption is glucose concentration dependent. Mechanisms regulating glucose-dependent increases in bone resorption have not been identified. Glucose activates p38 MAP-kinase in other cells and since MAP kinases activate transcription factors, we hypothesized that glucose-stimulated bone resorption may be modulated by increased expression of the vacuolar H(+)-ATPase. Glucose activates osteoclast p38 MAP-kinase in a time and concentration-dependent manner as determined by Western analysis with phospho-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 45 publications
1
21
0
1
Order By: Relevance
“…For instance, Graves and colleagues have elegantly demonstrated in ligature, calvarial and bone fracture models (in the presence and absence of infection) that hyperglycemia and TNF-α affect fibroblast and osteoblast apoptosis which contributes to in vivo cartilage and bone loss in models of type 2 diabetes and hyperglycemia (Alblowi et al, 2009; Alikhani et al, 2007; Desta et al,; Graves et al, 2005; He et al, 2004; Kayal et al, 2009; Kayal et al,; Kayal et al, 2007; Liu et al, 2006; Liu et al, 2004; Lu et al, 2003; Santana et al, 2003; Siqueira et al).While our data demonstrates an osteoclast-specific augmented function in the absence of hyperglycemic contributions, it is plausible that hyperglycemia may further contribute to osteoclast hyperactivity in T1D. Indeed, glucose is the primary energy source of the osteoclast and has been shown to augment osteoclast-mediated resorption via increases in V-ATPase expression (Larsen et al, 2005; Larsen et al, 2002). Furthermore, lack of insulin, now considered to be a bone anabolic agent, leads to decreased bone formation in patients with T1D (Thrailkill et al, 2005).…”
Section: Discussionmentioning
confidence: 50%
“…For instance, Graves and colleagues have elegantly demonstrated in ligature, calvarial and bone fracture models (in the presence and absence of infection) that hyperglycemia and TNF-α affect fibroblast and osteoblast apoptosis which contributes to in vivo cartilage and bone loss in models of type 2 diabetes and hyperglycemia (Alblowi et al, 2009; Alikhani et al, 2007; Desta et al,; Graves et al, 2005; He et al, 2004; Kayal et al, 2009; Kayal et al,; Kayal et al, 2007; Liu et al, 2006; Liu et al, 2004; Lu et al, 2003; Santana et al, 2003; Siqueira et al).While our data demonstrates an osteoclast-specific augmented function in the absence of hyperglycemic contributions, it is plausible that hyperglycemia may further contribute to osteoclast hyperactivity in T1D. Indeed, glucose is the primary energy source of the osteoclast and has been shown to augment osteoclast-mediated resorption via increases in V-ATPase expression (Larsen et al, 2005; Larsen et al, 2002). Furthermore, lack of insulin, now considered to be a bone anabolic agent, leads to decreased bone formation in patients with T1D (Thrailkill et al, 2005).…”
Section: Discussionmentioning
confidence: 50%
“…Earlier studies with chicken osteoclasts demonstrated that glucose, instead of fatty acids or ketone bodies, was the principle energy source for bone resorption, and that attachment to the bone surface greatly simulated glucose consumption by osteoclasts [54]. Glucose was further shown in chicken osteoclasts to stimulate both protein and mRNA levels of the vacuolar-type H + -ATPases (V-ATPase) essential for the resorptive activity of osteoclasts [55]. Similarly, limiting glucose metabolism by either omission of glucose in the culture media or knockdown of Hif1a reduced bone resorption by murine osteoclasts in vitro [48].…”
Section: Glucose Metabolism In Osteoclastsmentioning
confidence: 99%
“…We speculated that similar pathways could be involved in our model. Unlike the possible transcriptional-independent role of p38 MAPK, Larsen and colleagues have shown that glucose regulates osteoclast H + -ATPase expression by a mechanism involving p38 MAPK [21]. In our system, the increased activity of H + -ATPase in chronically Ang II-treated cells was not accompanied by changes in the expression of, at least, the B2 subunit of vacuolar H + -ATPase, suggesting that maybe p38 MAPK plays a role in the control of cytoskeleton proteins.…”
Section: Discussionmentioning
confidence: 93%